Psychological factors affecting the adaptation of preschool children to the social environment: The role of family and kindergarten environments - Nazаrova Dilnoza O‘razalievna (Goodwood Publishing, 2025)
Purpose: This study aims to identify the key psychological factors that influence preschool children’s adaptation to their social environment. Special emphasis is placed on the role of family and kindergarten settings in shaping personality development, emotional balance, and communication skills. Research methodology: The research employs a qualitative-descriptive approach, synthesizing existing psychological and pedagogical literature, along with practical observations from early childhood education contexts. Data sources include theoretical frameworks, empirical studies, and case-based insights from family and preschool environments. Results: The findings reveal that parenting style, parental emotional support, and consistent attention are critical for children’s emotional stability and self-confidence. Likewise, pedagogical practices in kindergarten, peer relationships, and interaction with educators play a significant role in strengthening communication skills and encouraging social activity. These combined factors create a supportive environment that enables smoother adaptation to new social conditions. Conclusions: Successful adaptation in early childhood relies on the synergy between family involvement and educational settings. The alignment of parenting practices and pedagogical approaches provides a foundation for personality growth, social competence, and emotional resilience in children. Limitations: The study is limited by its reliance on secondary sources and lacks longitudinal data to measure adaptation outcomes over time across diverse cultural settings. Contribution: This research provides practical recommendations for preschool educators and psychologists to design strategies that enhance children’s adaptation, thereby improving early childhood education quality and long-term social development.